Coaching the javelin - Pagani, Tom; Monterey Bay Video Production Co.; Coaches Choice (Monterey, CA : Monterey Bay Video Production : Coaches Choice [distributor], 2002)
Reviews the proper fundamentals and techniques for throwing the javelin, and also features an explanation and demonstration of the learning sequences and practical drills that can be used to help both the coach and the athlete better understand how to throw the javelin properly
Title from title screen
Keywords: Javelin throwing; Javelin throwing -- Training; Track-athletics -- Coaching; Coaching (Athletics)